A case report from non-endemic Australia on systemic melioidosis presenting with septic arthritis - Buddhika Dhananjalee Alahakoon; Monarita Handa; Shiromali Malalasekara (Infectious Medicine)
Clinical spectrum of melioidosis can vary from a simple skin infection and pneumonia to severe septicaemia with multiorgan failure. Bone involvement in melioidosis is generally low, and the major risk factor is the delay in diagnosing the primary site infection. We present a case of septic arthritis with primary lung melioidosis, whose diagnosis of pulmonary melioidosis was delayed for 5 weeks leading to a septicaemia and septic arthritis. This case highlights the importance of improved clinical awareness among health practitioners and a low threshold for radiological screening of high-risk patients, even in non-endemic areas. It also highlights the fact that having adjunctive open arthrotomy in managing joint infection in melioidosis improves the clinical response to treatment.